Red Hat Fedora core 6 unleashed - Hudson, Andrew, 1978- (Sams, 2006)
Red Hat® Fedora™ Core 6 Unleashed presents comprehensive coverage of Fedora Core 6, the popular Linux distribution developed by the Red Hat-sponsored Fedora Project. This book provides detailed information on installing, using, and administering Fedora. You'll learn how to set up a desktop workstation or a high-powered server, and you'll find complete details on Yum, Fedora's easy-to-use desktop and productivity software. Red Hat® Fedora™ Core 6 Unleashed covers a wide range of topics from using the software you need every day for work, such as the OpenOffice.org productivity suite and the Firefox web browser, to configuring your Linux desktop to run smoothly using multiple printers, shell scripts, and more. For the hardcore Linux enthusiast, there is complete coverage of the X Window system, Linux programming (including Mono), web server administration, and network administration. Install and configure Red Hat's Fedora Core 6 Linux distribution Manage Linux services and users Run a printer server with CUPS Connect to a local network and the Internet Set up and administer a web server with Apache Secure your machine and your network from intruders Rebuild and install a new Linux kernel Learn shell scripting Run other operating systems on Fedora with Xen Share files with Windows users using Samba Get productive with OpenOffice.org Play games on Linux Use Linux multimedia programs Use a database with Fedora Set up a firewall Watch television on your computer Set up a DNS server Andrew Hudson is a regular freelance contributor to Linux Format magazine, the UK's largest Linux magazine. His particular area of expertise is Fedora Core and the Red Hat Enterprise platform. Paul Hudson is a professional developer and full-time journalist for Future Publishing. His articles have appeared in Mac Format, PC Answers, PC Format, PC Plus, and Linux Format. DVD includes The full Fedora Core 6 binary distribution, packed with the complete Fedora Core packages The complete OpenOffice.org office suite Hundreds of additional programs and utilities Register your book at www.samspublishing.com/register for access to exclusive bonus content and other resources. Category: Operating Systems/Linux Covers: Fedora Core 6 Linux Distribution User Level: Intermediate-Advanced www.samspublishing.com.